Pengaruh Metode SPEOS (Stimulasi Pijat Endorphin, Oksitosin, dan Sugestif) dan Murottal Al-Qur’an terhadap Produksi Asi Ibu Post Sectio Caesarea - Arsi, Ranida; Afdhal, Fitri; Saputra, Andre Utama (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
ASI is an important food that babies need especially during the first 6 months of life. The success of exclusive breastfeeding is determined from the beginning of breastfeeding. There are many factors that hinder the production of breast milk, one of which is that mothers with casarean delivery are at 3 times greater risk of hampering the breastfeeding process. Apart from medicines, mothers also experience discomfort due to pain which makes the mother helpless and worries about her ang her baby’s helath. This is what will hinder the formation and excretion of breast milk. SPEOS method is a methods for breastfeeding and Murottal Al-Qur'an is a method to reduce anxiety and pain. This intervention not only looks at the mother physicallu but also psychologically. The purpose of this study was to determine the effect of SPEOS method and Murottal Al-Qur'an on Breast Milk Production of Post Sectio Caesarean mothers. This study was a quasy experiment with pretest-posttest control group design. Respondents were post sectio caesarean mothers who met the inclusion criteria. The number of respondents was 58 who were taken by consecutive sampling technique, and were divided into the intervention group and control group. The intervention was given at 24 hours after surgery for 2 days within 27 minutes, SPEOS method for 15 minutes and Murottal Al-Qur’an for 12 minutes. The intervention was carried out 2 times a day. The data were collected through the breast milk production assessment using observation sheet and analyzed using the Wilcoxon and the Mann-Whitney test. The results showed an increase in breast milk production after the intervention (p = 0.000 <0.05). SPEOS and Murottal AL-Qur'an methods indicated significant effect on breast milk production in post-sectio caesarean mothers p = 0.000 <0.05. Based on the results of the study, it is suggested that SPEOS method and Murottal Al-Qur'an could be used as alternative intervention to overcome the problem of milk production in post sectio caesarean mothers